Enhancing tensile and fatigue properties of additively manufactured alloys by post-processing heat treatment - Radhakrishnan, Jayaraj (Nanyang Technological University, 2022)
While investment in additive manufacturing has taken significant strides in the past few years, widespread industrial adoption is still at a slow pace due to the poor mechanical properties and lack of competency against conventionally manufactured (CM) counterparts. Amongst the different AM techniques, laser beam-powder bed fusion (LB-PBF) is the most abundantly investigated process due to its deep market penetration as well as the vast number of LB-PBF machine manufacturers. LB-PBF process results in a fine hierarchical microstructure which can impart a simultaneous enhancement of strength and fracture toughness. However, the pursuit to achieve simultaneous strength and toughness by novel processing strategies has led to an even larger variation in the reported mechanical properties of AM alloys fabricated using LB-PBF. In contrast, binder jet printing (BJP) process is relatively unexplored, and the process-structure-property correlations of alloys manufactured using this process are not widely reported despite being a lesser expensive fabrication alternative. In both the above mentioned AM systems, persistent presence of large pores – either lack of fusion, or keyhole pores or improper sintering via BJP, has hindered AM alloys to perform competitively against CM counterparts. While the overall pore fraction determines the tensile strength of the alloy, the highly angular shape of these individual pores increase the local stress concentration, initiate fatigue cracks, and bring down the fatigue strength significantly. Although several strategies are underway to enhance the mechanical behavior of AM alloys by reducing the overall fraction of pores, none of the recent studies focused on investigating the microstructure’s potential to resist crack and improve the fatigue properties of AM alloys. Furthermore, in alloys strengthened by precipitation hardening (PH), post processing heat treatments which can severely change the as-built microstructure, are required before being utilized in the intended application. To accelerate adoption of AM alloys in wider marketplace, in the current work, we – i) benchmarked the mechanical properties of AM alloys by studying machine-to-machine variation, ii) investigated the potential of AM microstructure to resist fatigue failure, iii) studied the cascading effects of post-processing heat treatment due to the diverse as-built microstructural features, and iv) enhanced the tensile and fatigue strength of AM alloys by appropriate post-processing treatments. Two alloys were considered for the current study – LB-PBF Inconel 718 and BJP 17-4PH martensitic stainless steel. The results of the work show that the LB-PBF induced microstructural characteristics such as solidification cells with high dislocation density are effective in resisting the growth of short fatigue crack (SFCs) at 600 °C, as compared to RT. Additionally, the fatigue strength was enhanced by standard solutionizing and aging heat treatment. However, the increase in fatigue performance was limited by persistence of pores and grain coarsening. To counter the sub-optimized improvement in mechanical properties of the first part, other heat treatments were explored. Additionally, to gain clarity about wide spectrum of mechanical properties of LB-PBF Inconel 718 reported in literature, tensile properties of as-built specimens fabricated using two different LB-PBF machines were considered. Amongst the five different heat treatment schedules examined, one set led to the retention of as-built grain morphology and texture with the formation of the δ phase. The second set of heat treatments led to complete recrystallization, and hence loss of as-built microstructural signatures, with no δ phase. The critical role of δ phase in determining the grain growth kinetics and subsequently the anisotropy in mechanical properties of heat-treated IN718 was elucidated. Implications of these results in terms of developing and designing the processing strategies of LB-PBF Inconel 718 with tailored microstructures and good mechanical properties were discussed. To address the research gap of the relatively unexplored BJP 17-4PH SS alloy, the microstructures, and mechanical properties of the martensitic (α’) stainless steel were investigated and compared with those of the conventionally manufactured (CM) alloy. The fraction of defects (like pores and δ-ferrite) in the alloy were controlled either by process parameters, or by post-processing heat treatments. Furthermore, the martensitic microstructure was tempered by post-fabrication over-aging heat treatment to improve strain hardening and substantially enhance ductility due to the formation of reversed γ films. The results of tensile tests and comparison to CM alloy behavior showed the strength and ductility to rise asymptotically with decrease in porosity until a critical fraction is reached. While the high cycle fatigue behavior was enhanced by reduction of porosity, HIP resulted in fatigue strength as good as CM counterparts due to reduction in pore size and dynamic recrystallization. More importantly, over-aging heat treatment substantially improved the fatigue resistance of 17-4PH alloy by increasing the stress intensity threshold for fatigue crack initiation. These variations are rationalized by recourse to analysis of the microstructure-crack interactions and was found that plasticity induced crack closure (PICC) and TRIP mechanisms are preferentially dominant at the fatigue crack tip of the over-aged microstructure. The significance of pore size rather than overall pore fraction on the high cycle fatigue resistance of BJP 17-4PH alloys was highlighted. Overall, the findings in this thesis contributed to the scientific knowledge that is essential to propel AM alloy usage in industry.